Evaluation of Functional Lower Urinary Tract Dysfunction in Children: Are the Physicians Complying with the Current Guidelines? - Mesrur Selcuk Silay; Ahmet Ruknettin Aslan; Erim Erdem; Zafer Tandogdu; Serdar Tekgul (The Scientific World Journal)
Objective. To elucidate whether the diagnostic and treatment approaches of the physicians for functional lower urinary tract dysfunction (LUTD) in children is complying with the current guidelines. Material and Methods. We have conducted an internet-based national survey for the physicians from different departments randomly sampled from the database of Turkish Paediatric Urology Society. Participants were asked to answer two-page questionnaire consisting of 4 main sections: “demography,” “working conditions,” “daily practice,” and “scientific knowledge.” Kruskal Wallis and multiple logistic regression were used for statistical analyses. Results. Of the 117 departments a total of 93 have completed the survey (n: 58 urology; n: 35 paediatric nephrology). Routine use of a questionnaire with validated symptom scoring system was found to be 13.9%. Of the participants, only 38.7% were asking all of the patients to fill the bladder diary. During treatment, only 24.7% were applying standard urotherapy for every patient. Almost half of the clinicians (45.1%) believed that they were personally insufficient during the evaluation of those children. Finally, 86% reported that children with LUTD were not adequately approached. Conclusions. Evaluation of LUTD in children is not complying with the current guidelines. General approach for those children needs to be revisited by the clinicians.